PROSPECTIVE ANALYSIS OF POLICY STRATEGY FOR HOSPITALS IN LOMBOK ISLAND - Sri Sulistiowati; Ida Ayu Nyoman Saskara (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
The government has made various policies to improve infrastructure in all public hospitals in Indonesia. Gradually, one by one government policies were introduced in order to improve health facilities, invest in modern medical equipment, and develop the most advanced specialties. The Government has undertaken an ambitious development and expansion of the health system to encourage community participation and initiatives in providing health services for. The polemic in health policy is related to problems in the health care system that often arise, namely cases of patient refusal. Furthermore, in the implementation in the field, the health services provided by the hospital are still problematic. Patients have to look for rooms from one hospital to another because the hospital is fully informed. This study tries to formulate problems (1) How is the relationship between government policy and public health and (2) How is the relationship between hospital performance and public health? This research is a literature review related to government policies in the health sector. Through the literature, this study tries to analyze the relationship between government policy and public healt h and the relationship between hospital performance and public health. The conclusions of this study are (1) the health services provided by the hospital are still problematic. Patients have to look for rooms from one hospital to another because they are fully informed by the hospital; (2) Hospital is one type of public sector service providing services in the health sector to the community whose performance needs to be measured. The concept of performance measurement in public sector organizations is aimed at helping public managers assess the achievement of a strategy through financial and non-financial measurement tools.